To solve the equation \( 46x^2 - 138x = 0 \) by factoring out the greatest common factor (GCF), we start by identifying the GCF of the terms in the equation.
The GCF of \( 46x^2 \) and \( -138x \) is \( 46x \). We can factor out \( 46x \):
\[ 46x(x - 3) = 0 \]
Next, we set each factor equal to zero:
- \( 46x = 0 \)
- \( x - 3 = 0 \)
From \( 46x = 0 \):
\[ x = 0 \]
From \( x - 3 = 0 \):
\[ x = 3 \]
Thus, the solutions are \( x = 0 \) and \( x = 3 \).
Therefore, the correct response is:
The solutions are x=0 and x=3.